Thermal degradation characteristic of Tetra Pak panel boards under inert atmosphere - Figen, Aysel Kanturk; Terzi, Evren; Yilgor, Nural; Kartal, Saip Nami; Piskin, Sabriye (KOREAN INSTITUTE CHEMICAL ENGINEERS, 2013)
Thermal degradation characteristics of Tetra Pak panel boards (TPPB) can be useful to improve usage of such panels as an alternative to wood-based products such as plywood, fiberboard, and particleboard. In the study, samples from the TPBBs manufactured from waste Tetra Pak packages (WTPP) were heated in a nitrogen atmosphere at different heating rates (10, 15 and 20 degrees C/min) using a thermal analysis system. The Coats-Redfern kinetic model was applied to calculate kinetic parameters. The degradation rate equations were then established. In addition, the kinetic compensation effect (KCE) was used to correlate the pre-exponential factor (k(o)) with activation energy (E-a) and the existence of the KCE was accepted. TG-FT/IR analyses were applied to the TPPB degradation and then the FT-IR stack plot was used to analyze gas products (CO2, CH4, HCOOH, and CH3OH). Infrared vibrational frequencies and the micro, crystal structure of the TPPBs were investigated by Fourier transform infrared spectroscopy (FT-IR), Scanning electron microscope (SEM) and X-Ray diffraction analysis (XRD), respectively.
Keywords: Tetra Pak; Panel Board; Thermal Degradation; Coats-Redfern; FT-IR; Chemistry; Engineering